Pemanfaatan Museum 13 Sebagai Sumber Belajar Sejarah Siswa SDN Panjunan II Melalui Ekstrakurikuler Kepurbakalaan - Marshanda Fitria Intan (HEURISTIK: Jurnal Pendidikan Sejarah, 2022)
An area that is rich in historical heritage objects is certainly an advantage to be proud of. The richer the history, of course, an area will certainly have advanced and many museums. One of the areas awarded with extraordinary historical objects is Bojonegoro Regency. Bojonegoro is an area where there are many historical relics, including paleontological objects such as ancient animal fossils. Therefore, it is not surprising that in Bojonegoro there are several museums, one of which is Museum 13 which focuses on paleontology. The existence of Museum 13 which is located in the Elementary School area has provided benefits for students, especially when the archaeological extracurricular was established which of course is used as a source of learning history for students. This study aims to describe Museum 13, how the process of establishing and implementing archaeological extracurricular activities and its use as a source of learning history for elementary school students. The method used is historical research method which is carried out in four stages. The first stage is heuristics or data collection, verification, interpretation, and writing of history or historiography.